Religia w obrębie rozumu postmetafizycznego - Józef Bremer (Jesuit University Ignatianum in Krakow, 2009)
Having presented the concepts of reason known from the history of philosophy, we shall concentrate on determining the place of religion within the scope of the so-called post-metaphysical reason. This expression, referring to "post-metaphysical thinking" of J. Habermas, will be of interest to us as far as the following: (I) the self-critical attitude of reason towards religious contents, (II) the possibility to translate them into the language of lay society and (III) the possibility to connect it with Christian theology.